Saputangan Sirah Baragi : New Hegemony of Minangkabau Modern Literature - Novi Yulia; Zurmailis Zurmailis; Khairil Anwar; Riyani Vadilla (Andalas International Journal of Socio-Humanities, 2019)
This paper seeks to reveal the existence of the modern literary genre of Minangkabau, in the repertoire of modern Indonesian literature. Modern Minangkabau literature was detected existed since the 1930s through the printed media of the time. But the genre only showed its entity in the 1960s through Nasrul Siddik's short stories recorded in Saputangan Sirah Baragi (1966). The anthology of this short story gives a firm limit to the existence of the Minangkabau modern literary genre, and the kaba genre by strengthening its epigons in local print media, such as writers in the Aman Makmur newspaper , Singgalang , Semangat , and so on in the modern Indonesian literary horizon. So that it becomes a new hegemony in the modern Minangkabau literature repertoire in particular.